Turbulent fluctuation moments of gas species concentrations in complex reaction systems. (21st September 2020) - Zhang, Jian
Highlights: The turbulent fluctuation moments of gas species concentrations are analyzed. The reaction source terms are found in the transport equations for these moments. The reaction source terms play a redistribution role in these equations. Abstract: Chemical reactions of gaseous fuel are significantly affected by turbulence during combustion processes. They should also impose influences on gas turbulence. The turbulent fluctuation moments of gas species concentrations are analyzed in complex reaction systems. Different multi-step or detailed reaction mechanisms are adopted for the combustion of gaseous fuel. The transport equation for the fluctuation moment of mixture fraction contains no reaction source term when the mixture fraction is a conserved scalar. The fluctuation moment of mixture fraction comprise a number of concentration fluctuation moments. The reaction source terms are found in the transport equations for all these concentration fluctuation moments. The concentration fluctuation moments are influenced by the chemical reactions, while the fluctuation moment of mixture fraction is not affected by the reactions. Thus the reaction source term plays not a production or dissipation role but a redistribution role in the equation for the concentration fluctuation moment.